2015
DOI: 10.1063/1.4917331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron addition on the structure and magnetic properties of CoPt nanoparticles

Abstract: Articles you may be interested inRecording-media-related morphology and magnetic properties of crystalline CoPt3 and CoPt3-Au core-shell nanoparticles synthesized via reverse microemulsion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The addition of noble metals in CoPt, in contrast to the FePt, does not affect the ordering temperature significantly; however, Sb doping reduces the ordering temperature, but still, an annealing at 400 °C is required to reach a 1 kOe coercivity at room temperature . Similarly, addition of B leads to coercivities of 12 kOe at room temperature after annealing at 600 °C for 2 h, close to the value reported at 700 °C for 2 h in the binary system, effectively reducing the annealing temperature by 100 °C . Following a one-step solid-state methodology, Bian et al reported the synthesis of L1 0 CoPt nanoparticles which reveal 3.2 kOe coercive field after a 550 °C annealing, but the particles lose their uniformity and show a broad distribution of particle size in the range of 10–19 nm.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…The addition of noble metals in CoPt, in contrast to the FePt, does not affect the ordering temperature significantly; however, Sb doping reduces the ordering temperature, but still, an annealing at 400 °C is required to reach a 1 kOe coercivity at room temperature . Similarly, addition of B leads to coercivities of 12 kOe at room temperature after annealing at 600 °C for 2 h, close to the value reported at 700 °C for 2 h in the binary system, effectively reducing the annealing temperature by 100 °C . Following a one-step solid-state methodology, Bian et al reported the synthesis of L1 0 CoPt nanoparticles which reveal 3.2 kOe coercive field after a 550 °C annealing, but the particles lose their uniformity and show a broad distribution of particle size in the range of 10–19 nm.…”
Section: Introductionmentioning
confidence: 55%
“…31 Similarly, addition of B leads to coercivities of 12 kOe at room temperature after annealing at 600 °C for 2 h, close to the value reported at 700 °C for 2 h in the binary system, effectively reducing the annealing temperature by 100 °C. 32 Following a one-step solid-state methodology, Bian et al 33 reported the synthesis of L1 0 CoPt nanoparticles which reveal 3.2 kOe coercive field after a 550 °C annealing, but the particles lose their uniformity and show a broad distribution of particle size in the range of 10−19 nm. Very recently L1 0 CoPt nanoparticles were synthesized via pyrolysis of metallopolymer precursors at 800 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Despite this thin surface layer, these small CoPt 3 NPs exhibit superparamagnetic behavior with a blocking temperature near 20 K and coercivity at 10 K of 27.9 kA m −1 (∼0.035 T, 350 Oe), which is in agreement with previous reports for similarly nanosized CoPt 3 particles. 51,52 However, there is also evidence of a second magnetic phase in the ZFC curve, possibly a small amount (∼4%) of CoO on the NP surface. This can, in fact, strongly enhance the magnetization compared with other reported NPs without significantly affecting their superparamagnetism.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…It has been well known that magnetic CoPt materials including CoPt NPs and thin films have a broad range of applications in recording media [20,21] and magnetic sensor [22]. Therefore, CoPt NPs are a good candidate to investigate the relationship between the magnetism and catalysis.…”
Section: Introductionmentioning
confidence: 99%